Factors associated with mortality among patients with tuberculosis in a tertiary hospital in South West Nigeria - Abimbola Ololade Odeyemi; Abiona Oluwadamilola Odeyemi; Abiodun Ronke Ojewuyi; Yetunde Toyin Olasinde; Opeyemi Olalekan Oni; Oluwafemi Tunde Ojo (Assam Journal of Internal Medicine)
Background: Tuberculosis (TB) is a significant cause of morbidity and mortality, particularly in developing countries. Objective: To identify the factors contributing to TB mortality. Materials and Methods: This is a retrospective review of TB patients managed at the TB Clinic of a Teaching Hospital in Southwest Nigeria, from January 2015 to December 2021. The patient’s demographic characteristics, TB type, and coinfection with human immunodeficiency virus (HIV) were studied. The factors associated with mortality were examined. Results: 1259 TB cases were studied, with a mean (standard deviation) age of 42.6 (16.33) years. There was a male predominance of 64.9%. One hundred and fifty-one subjects died while receiving treatment; hence, the mortality rate was 12.0%. Age (P: 0.000), HIV status (P: 0.028), sputum smear-negative (P: 0.038), and extra-pulmonary TB (P: 0.019) were factors with statistically significant association with TB mortality. Older age (odds ratio [OR]: 1.017, 95% confidence interval [CI]: 1.007–1.028, P: 0.001) and HIV-positive status (OR: 1.911, 95% CI: 1.083–3.372, P: 0.025) were found to be independently associated with TB mortality. Conclusion: The proportion of patients who die during TB treatment is still high, particularly among those with older age (>60 years) and those with HIV coinfection. Prevention of HIV infection will have a substantial impact on the reduction of TB burden and mortality. More attention should be given to TB patients who are elderly and those with HIV/TB coinfection in order to improve the disease outcome.